EVALUASI PELAKSANAAN PEMBELAJARAN PROGRAM STUDI DESAIN KOMUNIKASI VISUAL MSD YOGYAKARTA - Soraya Fatmawati; Ali Muhtadi (Jurnal Inovasi Teknologi Pendidikan, 2016)
Penelitian ini bertujuan untuk mengetahui kesesuaian antara pelaksanaan pembelajaran Program Studi (Prodi) DKV di ASRD MSD Yogyakarta dengan standar atau kriteria yang telah dirumuskan. Penelitian ini merupakan penelitian evaluasi dengan menggunakan model evaluasi kesenjangan. Subjek atau responden adalah Ketua Program Studi, dosen dan mahasiswa Prodi DKV MSD Yogyakarta. Penelitian ini dilaksanakan dengan menempuh 5 tahap, yaitu: penyusunan desain, penetapan kelengkapan program, pengumpulkan data, pengukuran tujuan atau analisis data, dan perbandingan. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi dianalisis menggunakan model analisis interaktif dari Miles dan Huberman. Data kuesioner dianalisis menggunakan teknik statistik deskriptif dengan skala 4. Hasil penelitian menunjukkan bahwa pelaksanaan pembelajaran pada Prodi DKV MSD Yogyakarta belum sesuai dengan Permendikbud No. 49 Tahun 2014. Hasil penilaian mahasiswa menunjukkan bahwa pelaksanaan pembelajaran di Prodi DKV MSD berada pada kategori baik dengan nilai 3,20. Pembelajaran di Prodi DKV MSD Yogyakarta perlu dilaksanakan sesuai dengan Permendikbud No. 49 Tahun 2014. Kata Kunci: pelaksanaan pembelajaran, perencanaan pembelajaranTHE EVALUATION OF INSTRUCTIONAL IMPLEMENTATION OF VISUAL COMMUNICATION DESIGN STUDY PROGRAM IN MSD YOGYAKARTA Abstract This research aims to determine the suitability of the instructional implementation in Visual Communication Design (VCD) Study Program of MSD Yogyakarta Design and Art Academy with standard or criteria which have been formulated. This research was an evaluation research study that refers to the discrepancy evaluation model. The subjects consisted of the head of study program, lecturers and students of VCD study program MSD Yogyakarta. The research was conducted in five stages: design preparation, determination of the program’s completeness, data collection, purpose measurement or data analysis, and comparison. Data were collected through observation, interviews, and document searches, and were analyzed using an interactive analysis model proposed by Miles and Huberman. The questionnaire data were analyzed using descriptive statistical analysis in the scale 4. The result of the study shows that instructional implementation in Visual Communication Design Study Program of MSD Yogyakarta is not suitable to the Minister of Education and Culture Regulation No. 49, 2014. The result of student assessment indicates that the instructional implementation in VCD MSD Yogyakarta is categorized good with the value of 3.20. The instructional implementation in Visual Communication Design Study Program of MSD Yogyakarta needs to be adjusted with the National Standards for Higher Education the Minister of Education and Culture Regulation No. 49, 2014 for the instructional implementation can be presented. Keywords: instructional implementation, instructional planning